1982
DOI: 10.1002/1097-0142(19820101)49:1<170::aid-cncr2820490134>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal metastases from malignant tumors of the lung

Abstract: Autopsy data of 423 cases of primary tumor of the lung over a 36-year period were evaluated for the presence of gastrointestinal tract metastases. Fifty-eight cases (14%) were found and were analyzed for histologic nature of tumor, anatomic location, symptomatology and complications. The most common histologic type of lung tumor causing gastrointestinal tract metastasis was squamous cell (19 cases, 33%), followed by large cell (17 cases, 29%), and oat cell (11 cases, 19%). The esophagus was the most common sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
205
4
4

Year Published

1983
1983
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(220 citation statements)
references
References 7 publications
7
205
4
4
Order By: Relevance
“…According to several autopsy studies, gastrointestinal metastasis of primary lung cancer occurs in 4.7-14.0% of cases (3)(4)(5). However, in past clinical studies, the incidence of gastrointestinal metastasis has been reported to be as low as 0.2-1.7% (5)(6)(7)(8), and in the current study, the clinical prevalence of gastrointestinal metastasis of lung cancer was ~0.33% (7/2,066).…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…According to several autopsy studies, gastrointestinal metastasis of primary lung cancer occurs in 4.7-14.0% of cases (3)(4)(5). However, in past clinical studies, the incidence of gastrointestinal metastasis has been reported to be as low as 0.2-1.7% (5)(6)(7)(8), and in the current study, the clinical prevalence of gastrointestinal metastasis of lung cancer was ~0.33% (7/2,066).…”
Section: Discussioncontrasting
confidence: 44%
“…However, the clinical incidence of gastrointestinal metastasis of lung cancer has been reported to be as low as 0.2-1.7% (3)(4)(5)(6)(7)(8). By contrast, the rate of metastasis of primary lung cancer to the gastrointestinal tract in autopsy studies is higher than the clinical frequency of gastrointestinal metastasis.…”
Section: Introductionmentioning
confidence: 96%
“…Even though all cell types of primary lung cancer may have metastasis to small bowel, Antler et al reported that gastrointestinal metastases were more common in cases where large cell and small cell histology was seen in the primary tumour. 4,5,13 While presentation of the small intestinal metastases may be as perforation, obstruction, malabsorption and/or haemorrhage, Leidich and Rudolph have explained the pathogenesis in that the tumour cells from the primary, spread to the bowel wall either by haematogenous or lymphatic spread. 7 The tumour replaces all or part of the bowel wall resulting in various symptoms: viable bulky tumour causes obstruction, necrotic tumour perforates, ulcerative lesions bleed and extensive mucosal surface involvement leads to malabsorption.…”
Section: Wall Is Unremarkable (H and E 4x Magnification)mentioning
confidence: 99%
“…Hasta ileum metastazı tanısı aldıktan sonra medikal onkoloji ile görü-şülerek genel durumunun toplaması ve sonrasında tekrar kemoterapi planlanması açısından poliklinik kontrolü önerilerek taburcu edildi. (3,4). Bizim olgumuzda da tutulan bölge ileumdu.…”
Section: Olguunclassified